Serum Cardiac Troponin I Concentrations in Dogs with Systemic Inflammatory Response Syndrome. (January 2015) - Hamacher, L.; Dörfelt, R.; Müller, M.; Wess, G.
<x xml:space="preserve">Abstract</x> Background Myocardial injury can be detected by cardiac troponin I (cTnI) concentration, which appears to be a predictor of short‐term death in critically ill patients. It is unknown if the best prognostic indicator of short‐term survival is cTnI measurement at admission or at later time points. Hypothesis/Objectives Measuring cTnI with a high‐sensitivity (HS) test at different time points after admission may be a better short‐term prognostic indicator than a single cTnI measurement at admission in dogs with systemic inflammatory response syndrome (SIRS). Animals Prospective, observational clinical study of 60 dogs with SIRS. Methods Cardiac troponin I concentration was measured in 133 serum samples, collected at days 1, 2, 3, and 5. Additionally, the acute patient physiologic and laboratory evaluation (APPLE) fast score was evaluated at admission. Prognostic capabilities of cTnI measurement and APPLE fast score for 28‐day mortality were assessed by receiver operating characteristic curve analysis. Results Forty‐one dogs with SIRS that survived 28 days had significantly lower serum cTnI concentrations at admission (median, 0.09 ng/mL; P = .004) and at the peak time point (median, 0.23 ng/mL; P = .01) compared to 19 nonsurvivors (median at admission, 0.63 ng/mL; median at peak, 1.22 ng/mL). Area under the curve to predict survival, using cTnI was similar at admission (0.732) and at peak (0.708), and was 0.754 for the APPLE fast score. Conclusions and Clinical Importance Increased cTnI concentration in dogs with SIRS is associated with poor outcome. Daily follow‐up measurement of cTnI concentration provides no additional prognostic information for short‐term mortality.